KNOWLEDGE, BARGAINING POWER, AND THE INSTABILITY OF INTERNATIONAL JOINT VENTURES - Inkpen, Andrew C.; Beamish, Paul W. (Academy of Management Review, 1997)
Although the high rate of instability of international joint ventures (IJVs) has been well documented, the underlying reasons for the instability need clarification. In this article, we develop a theoretical framework for instability of IJVs grounded in a bargaining power and dependence perspective. Instability is defined as a major change in partner relationship status that is unplanned and premature from one or both partners' perspectives. The core argument is that the instability of IJVs is associated with shifts in partner bargaining power. Shifts in the balance of bargaining power occur when partners of an IJV acquire sufficient knowledge and skills to eliminate a partner dependency and make the IJV bargain obsolete. Our primary focus is on the acquisition of local knowledge by the foreign partner and the impact that this acquisition of knowledge has on the stability of the IJV.